Effect of nanostructured carbon coatings on the electrochemical performance of Li1.4Ni0.5Mn0.5O2+x-based cathode materials - Kurilenko, Konstantin A.; Shlyakhtin, Oleg A.; Brylev, Oleg A.; Petukhov, Dmitry I.; Garshev, Alexey V. (Beilstein Journal of Nanotechnology, 2016)
Nanocomposites of Li1.4Ni0.5Mn0.5O2+x and amorphous carbon were obtained by the pyrolysis of linear and cross-linked poly(vinyl alcohol) (PVA) in presence of Li1.4Ni0.5Mn0.5O2+x. In the case of linear PVA, the formation of nanostructured carbon coatings on Li1.4Ni0.5Mn0.5O2+x particles is observed, while for cross-linked PVA islands of mesoporous carbon are located on the boundaries of Li1.4Ni0.5Mn0.5O2+x particles. The presence of the carbon framework leads to a decrease of the polarization upon cycling and of the charge transfer resistance and to an increase in the apparent Li+ diffusion coefficient from 10−16 cm2·s−1 (pure Li1.4Ni0.5Mn0.5O2+x) to 10−13 cm2·s−1. The nanosized carbon coatings also reduce the deep electrochemical degradation of Li1.4Ni0.5Mn0.5O2+x during electrochemical cycling. The nanocomposite obtained by the pyrolysis of linear PVA demonstrates higher values of the apparent lithium diffusion coefficient, a higher specific capacity and lower values of charge transfer resistance, which can be related to the more uniform carbon coatings and to the significant content of sp2-hybridized carbon detected by XPS and by Raman spectroscopy.
Keywords: carbon coatings; electrode materials; Li-ion batteries; nanocomposites; nanostructures